1999
DOI: 10.1017/s0007485399000498
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of clones of theMyzus persicaecomplex (Hemiptera: Aphididae) differing in their ability to transmit the potato leafroll luteovirus (PLRV)

Abstract: A prerequisite to studying the specific interactions involved in the persistent transmission of luteoviruses such as the potato leafroll virus (PLRV) is the characterization of both the virus and its vectors. A range of techniques was used to assess genetic differentiation among 27 clones belonging to the Myzus persicae complex (M. persicae (Sulzer), M. antirrhinii (Macchiati) and M. nicotianae Blackman) and showing different efficiencies in transmitting PLRV isolates. All M. persicae/M. nicotianae clones belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
35
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 34 publications
7
35
1
1
Order By: Relevance
“…This confirms the tendency for low genotypic variability in parthenogenetic populations of aphids, as observed in previous studies on M. persicae (Terradot et al, 1999;Guillemaud et al, 2003b;Vorburger et al, 2003) and on other species (eg Fuller et al, 1999;Simon et al, 1999;Delmotte et al, 2002;Papura et al, 2003). However, the variability found in our study is far lower than that found in three previous studies that dealt with clonal populations of M. persicae collected at the regional scale.…”
Section: Selection and Drift In Myzus Persicaesupporting
confidence: 92%
See 2 more Smart Citations
“…This confirms the tendency for low genotypic variability in parthenogenetic populations of aphids, as observed in previous studies on M. persicae (Terradot et al, 1999;Guillemaud et al, 2003b;Vorburger et al, 2003) and on other species (eg Fuller et al, 1999;Simon et al, 1999;Delmotte et al, 2002;Papura et al, 2003). However, the variability found in our study is far lower than that found in three previous studies that dealt with clonal populations of M. persicae collected at the regional scale.…”
Section: Selection and Drift In Myzus Persicaesupporting
confidence: 92%
“…G1 was frequent in all the populations analyzed, whatever their location over a large geographic area (northern half of France), which is similar in size to the studies cited above. None of the frequent MLGs that were detected among flying aphids caught in aerial suction traps in France in 2000 (Guillemaud et al, 2003b) nor the frequent p6 MLG observed by Terradot et al (1999) among French and Spanish samples of M. persicae were the same as G1.…”
Section: Selection and Drift In Myzus Persicaementioning
confidence: 78%
See 1 more Smart Citation
“…In a concurrent collaborative study, Terradot et al (1999) used nine microsatellite loci that were used in the present work (M35 A , M37 A , M40 A , M63 A , M77 A , M107 A , S16b A , S17b X , S23 A ), and identified 23 alleles in seven clones of European M. persicae. We found 20 of these alleles in our Australian collections.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, intraspecific generalist and specialist morphs or genotypes adapted to a wide range of unrelated and specialized food plants respectively, have also been reported from different geographical regions 5,[8][9][10][11] . The green peach-potato aphid, Myzus persicae, is of Asian origin like its primary host, Prunus persica (L.), but has become a world-wide pest of many food crops, especially vegetables like potato, tomato, eggplants and kale crops 12 , and a vector of many plant diseases 13 . In India, the species is known to live by asexual reproduction on 244 species of secondary hosts belonging to 56 plant families 14 .…”
mentioning
confidence: 99%